Vietnam’s rice sector is the key to meeting methane reduction targets - Nelson, Katherine; Wassmann, Reiner; Sander, Björn Ole (2022)
Rice production contributes almost half of Vietnam’s total methane emissions and is the center of action for reducing the powerful greenhouse gas. At the COP 26 Glasgow, Vietnamese Prime Minister Pham Minh Chinh joined more than 100 countries in signing a methane emission reduction pledge. While the numbers are pointing towards the target, this op-ed piece tackled the challenge of introducing a set of mitigation options to millions of farmers across Vietnam.